Who Goes on Disability when Times are Tough? The Role of Social Costs of Take-Up among Immigrants - Delia Furtado; Kerry L. Papps; Nikolaos Theodoropoulos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2019)
Social Security Disability Insurance (SSDI) take-up tends to increase during recessions despite the fact that the program is intended to insure against the possibility of a work-preventing disability, not job loss. We examine the role that social costs - such as taboos against receiving government benefits or the difficulty of obtaining information about the program within one's social circle - play in the decision to apply for SSDI in response to changes in economic conditions. We show that immigrants from country-of-origin groups that have lower social costs to participation, as measured by past SSDI participation rates for their origin group, are more sensitive to economic downturns than immigrants from high cost groups. We present evidence that this is mainly driven by differences across origin countries in norms regarding the importance of work, rather than by information sharing or taboos against cheating the government.
Keywords: H55; J61; I18; J15; 330; Disability Insurance; Immigrants; Unemployment Rates; Ethnic Networks